2017
DOI: 10.3329/jsr.v9i2.29644
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Mixed Convection in Square Lid-Driven with Internal Elliptic Body and Constant Flux Heat Source on the Bottom Wall

Abstract: The mixed convection in square lid-driven with internal elliptic body and constant flux heat source on the bottom wall is numerically simulated in this paper following a finite element method approach. The left moving wall and right moving wall are cold. The upper wall is insulated and so is the lower wall with heat flux located in the middle. The magnetic field of strength B is applied parallel to x-axis. Result is presented for different Richardson numbers (0.01 ≤ Ri ≤ 10) when Grashof numbers are (10 ≤ Gr ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Later, Munshi et al [18] extended their works by considering a mixed convection double lid-driven square cavity with an inside elliptic heated block. At the same time, a numerical study of mixed convection in square liddriven with an internal elliptic body and constant flux heat source on the bottom wall was presented by Munshi et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…Later, Munshi et al [18] extended their works by considering a mixed convection double lid-driven square cavity with an inside elliptic heated block. At the same time, a numerical study of mixed convection in square liddriven with an internal elliptic body and constant flux heat source on the bottom wall was presented by Munshi et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is governed by non-dimensional parameters like the Grashof number, Gr, and the Reynolds number, Re, which describe buoyancy and shear effects, respectively. Several heat transfer and mixed convective flow investigations have been previously undertaken, using various temperature gradient and enclosure geometries combinations [4][5][6][7][8][9][10]. Torrance et al [11] examined numerically fluid motion caused by a shifting upper wall inside a rectangular enclosure.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the variation of Rayleigh number and period of the heated portion influences the Nusselt number on convective structures. Munshi et al [15] investigated mixed convection in square lid-driven cavity with elliptic obstacle inside and imposed constant heat flux on the lower wall, they concluded that the mixed convection is mainly controlled by Richardson number (Ri), Grashof number (Gr) and Reynolds number (Re).…”
Section: Introductionmentioning
confidence: 99%